Implementation of passive and active power filters for harmonic mitigation - Mohd Arif B. Mat Omar (School of Electrical System Engineering, University Malaysia Perlis, 2011)
To design and simulate a typical harmonic source model, which is a three-phase induction motor drive system by implementing an ASD, by using the PSIM software application as the circuit design and simulation tool. This particular phase emphasizes on achieving the results of all the harmonic components generated throughout the system.